(untitled) (gjstudies, 2014)
This research examines the evolving role of Information Systems (IS) auditors instrengthening cybersecurity frameworks within U.S. banking institutions. As cyberthreats become increasingly sophisticated, the traditional audit functions have expanded to encompass proactive cybersecurity assessment, vulnerability detection,and infrastructure protection. Through a mixed-methods approach incorporatingsurvey data from 150 IS auditors across major U.S. banks and quantitative analysis of cybersecurity incident reports from 2010-2013, this study develops a comprehensive model for evaluating cybersecurity effectiveness. The research identifiesthree critical dimensions where IS auditors contribute significantly: framework assessment maturity, vulnerability detection capability, and infrastructure protectionefficacy. Results demonstrate that banks with highly integrated IS audit functionsexperience 42% fewer successful cyber intrusions and 67% faster incident responsetimes. The proposed Cybersecurity Audit Maturity Model (CAMM) provides astructured approach for quantifying audit effectiveness, with validation showingstrong correlation (r=0.83) between model scores and actual security outcomes.These findings underscore the strategic importance of IS auditors in safeguarding national banking infrastructure and offer practical frameworks for enhancingcybersecurity resilience in financial institutions.